Isolasi dan Karakterisasi Kitinase Akar Tusam (Pinus merkusii Jungh. et de Vriese) Roots yang Bersimbiosis dengan Fungi Ektomikoriza - A. Handayani; S. M. Wisyastuti; S. Margino (Universitas Gadjah Mada, 2005)
The experiment was aimed to detect the activity and characterize the chitinase of tusam root during ectomycorrhizal symbiosis. Tusam inoculated with tusam stands soil from Kaliurang as fungi inocula. Crude proteins were isolated from 4, 6, and 8 weeks age of tusam. Chitinase activity and isoform were detected using glycol chitin as a subtrat. The enzyme was purified by ammonium sulfat precipitation, dialysis, followed by gel filtration chromatography. The results showed that tusam prodced chitinasse with a molecular weight of approximately 52kDa. The optimum activity was at pH 5 and temperature of 30°C.